2020
DOI: 10.1002/ijgo.13295
|View full text |Cite
|
Sign up to set email alerts
|

Mental health status of pregnant and breastfeeding women during the COVID‐19 pandemic: A call for action

Abstract: Increased prevalence of depressive symptoms and anxiety among pregnant women and women in the early postpartum period was observed during the lockdown in Belgium. Obstetricians must take actions to safeguard perinatal mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
236
4
15

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(272 citation statements)
references
References 3 publications
17
236
4
15
Order By: Relevance
“…The Canadian study found an elevated rate of depression and anxiety symptoms among pregnant women in comparison with previous meta analyses [21]. In another study of 5866 pregnant and breastfeeding women during the lockdown period in Belgium, an elevated rate of depression and anxiety symptoms was reported in comparison with reported rates prior to the pandemic [23]. In fact, most studies were conducted in the COVID-19 epidemic early on or in the quarantine period when psychological well-being of pregnant women had been severely affected.…”
Section: Discussionmentioning
confidence: 69%
“…The Canadian study found an elevated rate of depression and anxiety symptoms among pregnant women in comparison with previous meta analyses [21]. In another study of 5866 pregnant and breastfeeding women during the lockdown period in Belgium, an elevated rate of depression and anxiety symptoms was reported in comparison with reported rates prior to the pandemic [23]. In fact, most studies were conducted in the COVID-19 epidemic early on or in the quarantine period when psychological well-being of pregnant women had been severely affected.…”
Section: Discussionmentioning
confidence: 69%
“…By comparison, Sri Lankan women displayed a higher rate of anxiety than that observed in Chongqing, despite the fact that Sri Lanka had successfully contained the spread of the virus at the time of the study (10.4% vs 17.5%). Other studies have also reported higher prevalence of perinatal and postpartum anxiety and depression during the COVID‐19 pandemic 6,7 …”
Section: Demographic Characteristics Frequency (%) N=257 Normal (%mentioning
confidence: 92%
“…Future studies could also qualitatively investigate the breastfeeding intentions of mothers who delivered during the pandemic. Given the impact of the lockdown on women's support and perinatal mental health [33,34], awareness of clinicians and governmental perinatal organizations is, however, required to ensure the emotional wellbeing of women and to safeguard perinatal and infant mental health in the wake of the pandemic.…”
Section: Future Perspectivesmentioning
confidence: 99%